2014
DOI: 10.1089/ten.tea.2013.0535
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neurons Accelerate Skin Reepithelialization via Substance P in an Innervated Tissue-Engineered Wound Healing Model

Abstract: Keratinocytes are responsible for reepithelialization and restoration of the epidermal barrier during wound healing. The influence of sensory neurons on this mechanism is not fully understood. We tested whether sensory neurons influence wound closure via the secretion of the neuropeptide substance P (SP) with a new tissue-engineered wound healing model made of an upper-perforated epidermal compartment reconstructed with human keratinocytes expressing green fluorescent protein, stacked over a dermal compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 28 publications
1
72
0
1
Order By: Relevance
“…Thanks to the high versatility of these tissue-engineered skin models, it was possible to perform a wound in the epidermis to analyze the effect of innervation on re-epithelialization in vitro, compared with a control without nerves. Wound closure was shown to be twice faster in presence of nerves, because of their release of substance P. Indeed, this effect was completely abolished after blocking the NK1 receptor for substance P with an antagonist (255). This experiment showed that nerves promote a direct enhancement of re-epithelialization, independently of their induction of neurogenic inflammation in vivo, which is well-known to improve wound healing (31).…”
Section: Skin Substitutesmentioning
confidence: 81%
See 1 more Smart Citation
“…Thanks to the high versatility of these tissue-engineered skin models, it was possible to perform a wound in the epidermis to analyze the effect of innervation on re-epithelialization in vitro, compared with a control without nerves. Wound closure was shown to be twice faster in presence of nerves, because of their release of substance P. Indeed, this effect was completely abolished after blocking the NK1 receptor for substance P with an antagonist (255). This experiment showed that nerves promote a direct enhancement of re-epithelialization, independently of their induction of neurogenic inflammation in vivo, which is well-known to improve wound healing (31).…”
Section: Skin Substitutesmentioning
confidence: 81%
“…The in vitro impact on nerve migration of any molecule or cells incorporated into the model can be analyzed by quantification of the number of sensory neurites (254). These neurons, whereas they were of mouse origin, were shown to release neuropeptides (substance P) efficiently modulating the human keratinocyte behavior (255). Thanks to the high versatility of these tissue-engineered skin models, it was possible to perform a wound in the epidermis to analyze the effect of innervation on re-epithelialization in vitro, compared with a control without nerves.…”
Section: Skin Substitutesmentioning
confidence: 99%
“…All these mechanisms may play a role in diabetic ulcer formation and would be interesting to study using this glycated 3D culture system adapted to the context of wound healing [67].…”
Section: Discussionmentioning
confidence: 99%
“…Severe skin injuries always come with damage to peripheral nerves, so innervated 3D skin reconstructions could be developed as optimal skin substitutes for the patients to restore neurological function. Sensory neurons in skin models could not only potentially restore the sensibility of the skin [46], but also accelerate keratinocyte reepithelialization through secreting the neuropeptide substance P [47]. As mature neurons are difficult to obtain from human bodies and do not proliferate significantly both in vitro and in vivo , hESC/hiPSC-derived NCSCs, which can provide a large number of peripheral neurons for the innervated dermal substitutes, have great clinical significance for human skin transplantation.…”
Section: Clinical Applications Of Ncscsmentioning
confidence: 99%